1973
DOI: 10.1161/01.res.32.2.206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Changes in Cycle Length on Diastolic Depolarization Produced by Ouabain in Canine Purkinje Fibers

Abstract: Isolated canine papillary muscle-false tendon tissue preparations stimulated at a cycle length of 630 msec were treated with ouabain (2.1 x 10 -7 M ) until an increase in the slope of diastolic depolarization of Purkinje fibers was produced. Then the effects of changes in cycle length on the slope were tested. Sustained shortening of the cycle length increased the slope, and sustained lengthening had the opposite effect. An abrupt decrease in cycle length caused by a stimulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(35 citation statements)
references
References 18 publications
4
31
0
Order By: Relevance
“…It has been reported that premature excitations enhance the amplitude of the OAPs and sometimes cause triggered activity (Davis, 1973;Cranefield and Aronson, 1974;Wit and Cranefield, 1976). Therefore, we tested the effect of premature excitation on the OAPs and found that it caused an increase in amplitude of the OAPs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that premature excitations enhance the amplitude of the OAPs and sometimes cause triggered activity (Davis, 1973;Cranefield and Aronson, 1974;Wit and Cranefield, 1976). Therefore, we tested the effect of premature excitation on the OAPs and found that it caused an increase in amplitude of the OAPs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Only since it has been suggested that they are important factors in digitalis-induced arrhythmias have these activities been studied in detail (Rosen et al, 1973;Davis, 1973;. OAPs induced by digitalis occur in Purkinje fibers, atrial specialized conducting tissues Hashimoto and Moe, 1973), and ventricular muscle fibers (Ferrier, 1976).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The delayed afterdepolarizations and triggered activity observed in our study were similar to those noted in other preparations. 8 [23][24][25][26][27] The amplitude and coupling interval of delayed afterdepolarizations were a function of the cycle length and number of preceding impulses, and were dependent on extracellular Ca' + concentration (figures 5 to 7).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the genesis of ouabain-induced arrhythmias, oscillatory afterpotentials leading to triggered activity in cardiac Purkinje fibers are con sidered to play a major role (13)(14)(15)(16)(17); the mechanisms whereby the afterdepolarization occurs in the presence of cardiac glycosides could be explained by a hypothesis that the excess Na+ entry and/or accumulation of internal Na+ resulted from inhibition of Na-K ATPase by ouabain increase internal Ca2+ through altered Na-Ca exchange. An increase in internal Ca2+, then, would activate non specific inward currents, and the inward cur rent is responsible for the genesis of the transient afterdepolarization (16,18).…”
Section: Aconitine-induced Arrhythmiasmentioning
confidence: 99%